2020
DOI: 10.1016/j.heliyon.2020.e04140
|View full text |Cite|
|
Sign up to set email alerts
|

Designing and evaluating an automated intravenous dosage medication calculation tool for reducing the time of stat medication administration in a pediatric emergency department

Abstract: Background: Urgent medications are regularly prescribed using the term "stat", which indicates that the medication should be administered within 30 min after it is ordered. However, many hospitals struggle to reliably administer stat medications within 30 min after they are ordered. This study involved developing and evaluating an automated intravenous dosage medication calculation tool (AIVDMCT) for reducing the time between the order and administration of stat medications to children at a pediatric emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The systematic search on Medline (Ovid) found 47 articles describing systemic defenses to prevent IV MEs published between June 2016 and October 2021 (Supplementary file 3, http://links.lww.com/JPS/A612). The studies were conducted in the United States (n = 16), 47–62 the United Kingdom (n = 7), 63–69 Australia (n = 3), 70–72 Brazil (n = 3), 73–75 Spain (n = 3), 76–78 Mexico (n = 2), 79,80 Saudi Arabia (n = 2), 81,82 Singapore (n = 2), 83,84 Canada (n = 1), 85 China (n = 1), 86 France (n = 1), 87 Germany (n = 1), 88 Italy (n = 1), 89 Netherlands (n = 1), 90 and Switzerland (n = 1) 91 . Some studies (n = 2) were carried out in multiple countries 92,93 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic search on Medline (Ovid) found 47 articles describing systemic defenses to prevent IV MEs published between June 2016 and October 2021 (Supplementary file 3, http://links.lww.com/JPS/A612). The studies were conducted in the United States (n = 16), 47–62 the United Kingdom (n = 7), 63–69 Australia (n = 3), 70–72 Brazil (n = 3), 73–75 Spain (n = 3), 76–78 Mexico (n = 2), 79,80 Saudi Arabia (n = 2), 81,82 Singapore (n = 2), 83,84 Canada (n = 1), 85 China (n = 1), 86 France (n = 1), 87 Germany (n = 1), 88 Italy (n = 1), 89 Netherlands (n = 1), 90 and Switzerland (n = 1) 91 . Some studies (n = 2) were carried out in multiple countries 92,93 .…”
Section: Resultsmentioning
confidence: 99%
“…A lot of variation between the study designs and research methods was identified (Supplementary file 3, http://links.lww.com/JPS/A613). The designs used in more than one study were observational simulation studies (n = 8), 48,53,67,83,85,88,89,91 retrospective analysis of drug preparation reports (n = 6), 47,51,57,59,60,93 mixed-methods studies (n = 5), 63,64,68,69,76 observational studies (n = 5), 49,50,56,58,81 retrospective analysis of smart infusion pump alert log data (n = 5), 55,62,77,80,82 studies measuring costs or cost effectiveness of the studied defense (n = 4), 66,74,87,90 observational intervention studies (n = 3), 61,71,73 retrospective or observational studies measuring drug consumption (n = 2), 52,79 chart reviews (n = 2), 70,72 and studies to design and develop systemic defenses (n = 2) 65,92 . Other methods included an analysis of administration error reports (n = 1), 54 a survey study (n = 1), 84 healthcare failure mode and effects analysis (HFMEA) (n = 1), 86 a systematic review (n = 1), 78 and a systematic review with a meta-analysis (n = 1) 75 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations